2022
DOI: 10.1017/sjp.2022.2
|View full text |Cite
|
Sign up to set email alerts
|

What is the Current and Future Status of Digital Mental Health Interventions?

Abstract: The prevalence of mental disorders continues to increase, especially with the advent of the COVID-19 pandemic. Although we have evidence-based psychological treatments to address these conditions, most people encounter some barriers to receiving this help (e.g., stigma, geographical or time limitations). Digital mental health interventions (e.g., Internet-based interventions, smartphone apps, mixed realities -virtual and augmented reality) provide an opportunity to improve accessibility to these treatments. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 69 publications
(75 reference statements)
0
19
0
Order By: Relevance
“…Emerging technologies, including AI, were considered in our search strategy, but were not used by the OeMH interventions described in the included studies. Nonetheless, this knowledge area is expected to increasingly feature the use of emerging technologies in the near future as the focus extends beyond nascent explorations of their applications for mental health and investigates the optimization of their implementation as well [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging technologies, including AI, were considered in our search strategy, but were not used by the OeMH interventions described in the included studies. Nonetheless, this knowledge area is expected to increasingly feature the use of emerging technologies in the near future as the focus extends beyond nascent explorations of their applications for mental health and investigates the optimization of their implementation as well [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature demonstrates the importance of personalization from analyses of user reviews ( 58 ). Further reports posit that a lack of perceived personalization in DMHIs constitute a barrier to user engagement ( 59 , 96 ), and that offering personalized feedback increases user engagement ( 97 ). Therefore, by ensuring that the report content is personalized to the data provided by the user during the completion of the assessment, engagement may be increased.…”
Section: Discussionmentioning
confidence: 99%
“…By leveraging cutting-edge technology, these interventions facilitate more effective, efficient and adaptable communication strategies, which are critical for team success. Relative to traditional face-to-face interventions, digital workplace interventions generally come with peculiar challenges, including, for example, users’ engagement and adherence, ethics, privacy and data protection (Baños et al , 2022; Phillips et al , 2019). On the contrary, digital interventions for teamwork can offer unique advantages over traditional face-to-face interventions, such as increased geographical and temporal accessibility, cost-effectiveness, personalization and attractiveness (ibid).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Digital workplace interventions can be defined as structured, planned and science-based actions aiming to promote desirable work outcomes by exploiting the potential offered by digital technologies. It may be adaptations of traditional, in-person interventions facilitated through online teleconferencing platforms or designed exclusively for computer or smartphone applications (Baños et al , 2022). Although research has shown that digital interventions can effectively promote desirable workplace outcomes (Phillips et al , 2019), and despite promising preliminary evidence regarding the effectiveness of digital-based team coaching interventions in various industries (Bernardová, 2012; Franc et al , 2019; Tetour, 2019), much of the existing literature has primarily focused on individual-level implementation and evaluation of digital workplace interventions.…”
Section: Introductionmentioning
confidence: 99%